(untitled) (Education in the 21st Century, 2025)
Today, society needs active, self-confident people who keep up with the times and are able to promote new social initiatives and projects. Teacher leadership training is a consistent and step-by-step process that is important to organize through formal, non-formal education and learning processes. They will help ensure that teachers themselves are active participants in self-development programs and act as community leaders who contribute to the organization of the educational cause. A unique role in the development of teachers’ leadership potential should be assigned to higher education institutions, which, when organizing vocational education, take into account the interests of both the individual and society and the state as a whole, fulfilling the order of the country’s educational policy․ With teachers with high leadership potential, it is possible to create a democratic student-centered educational environment in which students participate in specially organized pedagogical activities aimed at gaining leadership experience. Teacher-leader everyone will be able to take different positions in social interaction, from student to teacher, from performer to organizer․ The purpose of this article is to analyze the role of teacher-leaders in the context of student-centered changes in the educational environment.